KAJIAN POTENSI HUTAN MANGROVE DI LAMPUNG MANGROVE CENTER (LMC) UNTUK PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT - Rusita Rusita; L. Elly; Rustiati Rustiati; Gunardi Djoko Winarno; Bainah Sari Dewi; Cahyaning Windarni (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
Forest provides basic ecosystem services to adjacent local people welfare. Ecotourism is one of the goverment program to improve the livelihood, by full local people involvement on planning, management and evaluation. Margasari, East L ampung, with its 700 ha mangrove forest, has a ahigh potential natural resources to develop community based ecotourism program. Study on evaluating mangrove forestas community based ecotourism was conducted in Lampung Mangrove Center, Margasari, East Lampung. collected data were analyzed qualitatively using SWOT with hope to obtain a mangrove forest potential for community-based ecotourism development. Potential of mangrove forests in LMC into category medium. Total of 98 % agreed if the community perception was developed as a community-based ecotourism. Motivation tourists visiting as much as 27 % for research, 37 % for recreation and rest along the mangroves by boat (36 %). LMC real carrying capacity of area can accommodate as many as 170 people / day, while the carrying capacity of the facility and amenitas 174 people / visit. SWOT analysis illustrates the mangrove forests in LMC has potential to be developed as a community-based ecotourism destination.